Abdominal wall reconstruction using anterolateral thigh flap with microsurgical pedicle lengthening technique: A case report. Issue 6 (27th July 2020) - Kim, Suhwan; Lee, Kyeong‐Tae
Abstract: Pedicled anterolateral thigh (ALT) flap has been employed for coverage of low abdominal wall defects. However, its use is limited for defects located more on the cranial side because of insufficient pedicle length. We present a case of successful reconstruction of mid‐abdominal wall defect using pedicled ALT flap, overcoming the issue of pedicle length shortage with a microsurgical pedicle lengthening technique. A 75‐year‐old man suffered from a 12 × 8 cm full‐thickness soft tissue defect on his mid‐abdominal wall originated from colon anastomosis site leakage after ileostomy takedown surgery. A pedicled ALT flap was planned for the defect coverage. After we performed debridement to prepare the wound bed, a 14 × 8.5 cm sized ALT flap based on two lateral circumflex femoral artery (LCFA) perforators was elevated. During intramuscular dissection of perforators, we dissected the distal portion of the LCFA descending branch. After full dissection of the pedicle to source vessels, we attempted to transfer the flap, but still the flap had short pedicle. We transected the pedicle just distal to the bifurcating point and reconnected it to the distal end of the dissected descending LCFA branch with microsurgical anastomosis. We passed the flap through a subcutaneous tunnel and conducted smooth flap insetting without any tension on the lengthened pedicle. Postoperatively, the wound healed successfully without complications. The patient was discharged 2 weeks after surgery and followed up at postoperative 3 months without adverse events. A local ALT flap with pedicle lengthened might be a reliable option for reconstruction of supraumbilical abdominal defects.